Current Trends of Cultural Diversity and Cultural Awareness: A Bibliometric Analysis - Azmi, Muhammad; Marfuah, Siti; Rahuma, Aulia (KnE Social Sciences, 2024)
This study analyzed research trends on cultural diversity awareness between 2019 and 2023 using bibliometric analysis on the Scopus database. Out of 1037 documents, we retrieved 336 articles meeting specific criteria from Scopus-indexed international journals. We used Mendeley for reference management and VOSviewer to classify and visualize the data. The data were classified into nine clusters using VOSviewer, offering valuable insights for future research in this field. The analysis provides a comprehensive overview of the current state and cultural diversity awareness research trends, highlighting the importance of continued exploration. Keywords: bibliometric analysis, cultural diversity, cultural awareness